2006
DOI: 10.3102/0013189x035008030
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers for Dialectally Diverse Classrooms

Abstract: Scholarship on dialect diversity in classrooms has yielded two seemingly incompatible lines of research. Although numerous pedagogical approaches have been shown to provide productive alternatives to traditional responses to stigmatized dialects, research on public perceptions and teachers’ attitudes suggests that negative beliefs about stigmatized dialects and the students who speak them are deeply entrenched in U.S. society. The authors argue that teacher preparation grounded in socio-linguistic understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 36 publications
1
72
0
2
Order By: Relevance
“…This was in part because the majority of preservice teacher literature focuses on the need to prepare an increasingly White, female, middle class, and monolingual teaching force to effectively teach a growing culturally and linguistically diverse student population (Godley, Sweetland, Wheeler, Minnici, & Carpenter, 2006;Gomez, 1993Gomez, , 1996Zumwalt & Craig, 2005). An immediate concern for preservice teacher education research and practice should be how to prepare the current homogeneous teaching force for teaching a culturally and linguistically diverse student population.…”
Section: Racial and Linguistic Diversity In Teacher Education Literaturementioning
confidence: 97%
“…This was in part because the majority of preservice teacher literature focuses on the need to prepare an increasingly White, female, middle class, and monolingual teaching force to effectively teach a growing culturally and linguistically diverse student population (Godley, Sweetland, Wheeler, Minnici, & Carpenter, 2006;Gomez, 1993Gomez, , 1996Zumwalt & Craig, 2005). An immediate concern for preservice teacher education research and practice should be how to prepare the current homogeneous teaching force for teaching a culturally and linguistically diverse student population.…”
Section: Racial and Linguistic Diversity In Teacher Education Literaturementioning
confidence: 97%
“…Although shaping English teachers' knowledge and beliefs about language variation is essential to improving their instruction, such efforts must be coupled with learning sociolinguistic PCK (Ball & Bass, 2000;Godley et al, 2006;Shulman, 1986;Sweetland, 2006). Sociolinguistic PCK for ELA teachers includes (but is not limited to) accurately explaining features of dialects and grammatical patterns; evaluating students' language choices; developing students' competency in Standardized Written English; and teaching about systems of power and privilege (Haviland, 2008;McIntosh, 1988) that are maintained via language ideologies.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
“…Even when there is training, there is no guarantee that there will be access. For example, in the U.S. Godley et al (2006) lament that despite the fact that language informs every aspect of the teaching/learning dynamic, nearly 1/3 of the teachers in the Language Arts profession have never taken a course in language diversity or Linguistics. Likewise, as Eastern Caribbean teachers of English, rather than being taught how to design lesson plans of inclusion, we are trained, covertly and overtly, to see learners as a homogeneous group who require generic training.…”
Section: Diversity Trainingmentioning
confidence: 99%
“…Ball and Muhammad (2003) previously cited, actually found that such courses helped teachers become more tolerant of language variation in the classroom, and so they recommend that 'at least one course dealing with language variation, bilingualism, and global linguistic diversity…be required of all students in teacher education programs' (p. 81). Godley et al (2006) are very specific about how language variation/diversity should be addressed in such programmes. They cite three themes that should be included in any such course:…”
Section: Diversity Trainingmentioning
confidence: 99%